The core of board networks and firm value - Park, A-Young; Oh, Gabjin (Frontiers in Physics, 2023)
We examine the statistical and dynamic properties of board networks connected through interlocking directorates. We find that the degree distribution of a board network follows a power-law distribution. Furthermore, the evolution of the core-periphery structure of board networks over time is related to market stability. This result implies that firms, when densely connected to other boards, would like to keep their position as core groups in board networks. Firm value shows a statistically positive relationship with firms centrally positioned in a board network. Overall, we suggest that board networks can help us understand market stability and serve as an alternative information channel for increasing firm value. These findings imply that the statistical and dynamic properties of board networks uncover information transmission during the global financial crisis. This paper contributes to interdisciplinary applications of physics in economics and finance in terms of the dynamics of a core-periphery structure of board networks.